Fish at Night and Birds by Day (Kemit VIII) - Klotz, David (Zeitschrift für ägyptische Sprache und Altertumskunde, 2009)
A new interpretation of Kemit VIII. The unusual expression “fish at night and birds by day” may allude to the solar cycle, not to fishing and fowling. This reading suggests that the protagonist, Au, is deceased, and not cavorting with a harem woman in Memphis as previous translations have assumed.